Relationships between Endogenous Plasma Biomarkers of Constitutive Cytochrome P450 3A Activity and Single‐Time‐Point Oral Midazolam Microdose Phenotype in Healthy Subjects. Issue 4 (14th October 2015) - Woolsey, Sarah J.; Beaton, Melanie D.; Choi, Yun‐Hee; Dresser, George K.; Gryn, Steven E.; Kim, Richard B.; Tirona, Rommel G.
Abstract: Due to high basal interindividual variation in cytochrome P450 3A (CYP3A) activity and susceptibility to drug interactions, there has been interest in the application of efficient probe drug phenotyping strategies, as well as endogenous biomarkers for assessment of in vivo CYP3A activity. The biomarkers 4β‐hydroxycholesterol (4βHC) and 6β‐hydroxycortisol (6βHCL) are sensitive to CYP3A induction and inhibition. However, their utility for the assessment of constitutive CYP3A activity remains uncertain. We investigated whether endogenous plasma biomarkers (4βHC and 6βHCL) are associated with basal CYP3A metabolic activity in healthy subjects assessed by a convenient single‐time‐point oral midazolam (MDZ) phenotyping strategy. Plasma 4βHC and 6βHCL metabolic ratios (MRs) were analysed in 51 healthy adult participants. CYP3A activity was determined after administration of an oral MDZ microdose (100 μg). Simple linear and multiple linear regression analyses were performed to assess relationships between MDZ oral clearance, biomarkers and subject covariates. Among study subjects, basal MDZ oral clearance, 4βHC and 6βHCL MRs ranged 6.5‐, 10‐ and 13‐fold, respectively. Participant age and alcohol consumption were negatively associated with MDZ oral clearance ( p = 0.03 and p = 0.045, respectively), while weight and female sex were associated with lower plasma 4βHC MR ( p = 0.0003 and p = 0.032, respectively). Neither 4βHC nor 6βHCL MRs were associated with MDZ oral clearance. Plasma 4βHC and 6βHCL MRs do not relate to MDZ single‐time‐point metabolic phenotype in the assessment of constitutive CYP3A activity among healthy individuals.